Hispanic Youth Visits to Food and Beverage Company Websites - Maia Hyary; Jennifer L. Harris (Mary Ann Liebert, 2017)
Purpose: To measure disparities in exposure to food/beverage websites by Hispanic youth. Methods: Observational study using market research panel data compared frequency and time spent visiting food/beverage websites and the Internet overall for Hispanic and non-Hispanic children (6?11 years) and youth (6?17 years). Results: Hispanic children and youth, particularly Spanish-speaking youth, were less likely to visit the Internet overall, but more likely to visit food/beverages websites, compared with their non-Hispanic peers. Conclusions: Food and beverage company websites disproportionately appeal to Hispanic youth. Public health advocates and companies should take action to reduce Hispanic youth exposure to unhealthy food marketing online.